DINAMIKA ISLAM DI YOGYAKARTA PRA-PASCA KEMERDEKAAN: ANALISIS HISTORIS ATAS RELASI KERATON DAN MUHAMMADIYAH - Aisyah Sacra Ali; Nabita Syifaur Rahmah (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2026)
This study examines the dynamics of Islamic development in Yogyakarta through a historical analysis of the relationship between the Yogyakarta Palace and Muhammadiyah during the pre- and post-independence periods. The research is grounded in the need to understand how traditional authority and modernist Islamic movements jointly shaped the religious character of Yogyakarta society. The study aims to describe the patterns of interaction between these two institutions and to identify their influence on socio-religious developments in the region. A historical research method with a qualitative approach was employed, involving archival exploration, literature review, and descriptive-analytical data interpretation. The findings indicate that in the pre-independence era, the Yogyakarta Palace and Muhammadiyah maintained a harmonious relationship through cultural adaptation and selective acceptance of religious reform. In the post-independence era, this relationship evolved into a more structural collaboration, reflected in joint contributions to education, health services, and social development. The study concludes that the interaction between the Palace and Muhammadiyah has been a crucial factor in shaping the distinctive model of Islam in Yogyakarta—modern, rational, yet firmly rooted in Javanese cultural tradition.